2016
DOI: 10.1155/2016/9706781
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Cooperative Spectrum Sensing under Guaranteed Throughput Constraints for Cognitive Radio Networks

Abstract: One of the main challenges in cognitive radio networks is the ability of secondary users to detect the primary user presence with high probability of detection. In previous research, optimizing cooperative sensing in cognitive radio networks is performed for either a targeted probability of detection or a false alarm. After setting one of the probabilities as an optimization constraint, the other is optimized. In this paper, a guaranteed constant throughput at the secondary users is introduced as a target whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…We denote the traffic demand of node n as T D (n), and it can have any bounded value as in (10). We denote the traffic demand of node n as T D (n), and it can have any bounded value as in (10).…”
Section: Constraints and Evaluation Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…We denote the traffic demand of node n as T D (n), and it can have any bounded value as in (10). We denote the traffic demand of node n as T D (n), and it can have any bounded value as in (10).…”
Section: Constraints and Evaluation Modelsmentioning
confidence: 99%
“…The traffic demand of node n also can be different with those of other member nodes. We denote the traffic demand of node n as T D (n), and it can have any bounded value as in (10). We assume that a CR network has a predetermined maximum data rate for each member node.…”
Section: Constraints and Evaluation Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this issue, multiple cognitive radios can be coordinated to perform spectrum sensing cooperatively. Several works [1][2][3][4][5][6][7] have shown that cooperative spectrum sensing can greatly increase the probability of detection in fading channels. In general, cooperative spectrum sensing is performed as follows: -Step 1: Every cognitive radio performs local spectrum measurements independently and then makes a binary decision.…”
Section: Introductionmentioning
confidence: 99%
“…8 For maximizing the throughput for SUs avoiding the collision trade-off between sensing accuracy and transmission of data is described in Zhang et al 9 and Al-Doseri. 10 For maximizing the utilities and many multiobjective functions, 11 scientists took help of metaheuristic algorithms [12][13][14] like genetic algorithm (GA) in Balieiro et al, Kamran and Moessner, and Khalid and Anpalagan. [15][16][17][18] To solve the problem of channel allocation, game theory 19 technique has been proposed.…”
mentioning
confidence: 99%